Development Of Papua Contextual Drama Scripts Based on Digital E-Comics in SMP Negeri 3 Manokwari (Catharsis, 2022)
In the era of revolution 4.0 to 5.0, changes and developments in science are growing. It has an impact in all areas of development, from politics, economics, to the world of education. In the world of education, teachers must carefully prepare adequate media and learning models according to the development of education. Revolutionary education 4.0 is known as 21st-century learning, a digital learning system. Digital learning is a challenge for schools in Papua. Therefore, this research presented a digital-based learning media solution. This research employed the development research of Dick and Carey (2021), which follows six stages of research. This study has examined the level of validity and reliability of expert reviews. The research resulted in developing learning media for Papuan contextual drama scripts based on digital e-comics for SMP Negeri 3 Manokwari class IX students. The experts have reviewed the product with a total of 4 experts. The results reviewed by experts have produced valid validity and reliable reliability for Papuan contextual drama script products. They are believed to help learn Cultural Arts in Papuan schools.